Instructed early SLA – development of attitudes - Mihaljević-Djigunović, Jelena; Letica Krevelj, Stela (2011)
The paper focuses on attitudinal development of Croatian young learners of English as L2. A longitudinal study carried out as part of the Early Language Learning project is described. Data collected during three years of following development of young learners’ attitudes to learning, teaching and using English, and development of their linguistic self-confidence are analysed and interpreted. The findings point to dynamic changes over time in all the investigated variables.
Projekt MZOS
ENG